EL tratamiento digital de imagenes como una herramienta de evaluación y análisis en la restauración y conservación del patrimonio arquitectónico = DIGITAL IMAGE MAPPING AS An Analisis and Evaluation Tool in Heritage Conservation and Restoration Process - Prendes Rubiera, Nicanor (Revista electrónica ReCoPar, 2006)
AbstractTwo monuments representative of the pre-Romanesque style are analyzed by digital image mapping integrating the results in a GIS. These buildings share various characteristics and have in common the pathologies (dark patinas, sugaring) and mainly the present fragmentary state they show. Regarding thisanalysis the areas of affection are quantified and mapped, establishing a cause-effect link between the petrophysical parameters of the materials (lithological varieties) and the changes developed. In addition, on one of the monuments, the missing original volumes are recreated by inferring the measurements from the preserved parts of the building. This process is based on the algorithms of texture generation, bymathematical morphology, and by the geometrical proportions on which the aesthetic pattern of the monument is based.